New cationic heptamethinecyanine-graphene hybrid materials. (April 2020) - Prousis, Kyriakos C.; Canton-Vitoria, Ruben; Pagona, Georgia; Goulielmaki, Maria; Zoumpourlis, Vassilis; Tagmatarchis, Nikos; Calogeropoulou, Theodora
Graphical abstract: Image 1 Highlights: Four near-infrared fluorescent indolenine-based cationic heptamethinecyanine dyes and their hybrids with exfoliated graphene were prepared. The substitution on the tricarbocyanine core and the linkage with exfoliated graphene affects the physicochemical and optical properties. Both the NIR-dyes and the graphene-based hybrid materials were able to enter the cells with a high efficacy. The graphene-based hybrid materials didn't show toxicity against RKO cancer cell line and the WJ-MSC human umbilical cord mesenchymal stem cells even at the highest concentrations tested.